Readiness of European laboratories for the revised EU Ambient Air Quality Directive: An interlaboratory comparison on levoglucosan, mannosan and galactosan in PM2.5 - Falk Mothes; Laurent Poulain; Jean-Luc Jaffrezo; Sophie Darfeuil; Rhabira Elazzouzi; Karl Espen Yttri; Hans Gundersen; Nicolas Bonnaire; Jean-Eudes Petit; Benjamin Bergmans; Eric Moïs; Theodoros Potouridis; et al. (Atmospheric Environment, 2026)

SIMTEGRAL: A framework for integrating process simulation data in life cycle sustainability assessment studies - Jan-Linus Popien; Abdur-Rahman Ali; Nur Ain Adibah binti Jamaludin; Alexander Barke; Steffen Blömeke; Christoph Herrmann; Thomas S. Spengler (Resources, Conservation and Recycling, 2026)

Corrigendum to “The pressure balancing act in geological storage: sharing the subsurface for the common good” [Int. Journal of Greenhouse Gas Control 151 (2026) 104610] - Audrey Ougier-Simonin; Owain Tucker; Alexander Bump; Sarah E. Gasda; Rannveig Elise Otterlei; Adriana Lemgruber-Traby; Eric Mackay; Ludovic Paul Ricard; Felix Herrmann; Matthias Imhof (International Journal of Greenhouse Gas Control, 2026)

The pressure balancing act in geological storage: sharing the subsurface for the common good - Audrey Ougier-Simonin; Owain Tucker; Alexander Bump; Sarah Eileen Gasda; Rannveig Elise Otterlei; Adriana Lemgruber-Traby; Eric Mackay; Ludovic Paul Ricard; Felix Herrmann; Matthias Imhof (International Journal of Greenhouse Gas Control, 2026)

Rainwater-driven transport of matter and microbes from phyllosphere to soil in a temperate beech forest - Markus Krüger; Karin Potthast; Beate Michalzik; Alexander Tischer; Martina Herrmann (Science of The Total Environment, 2025)

A heuristic approach to attenuation of non-relevant metabolites in groundwater and drinking water in Germany - Robin Sur; Marco Herrmann; Namjil Ganbaatar; Alexander Singer (Journal of Consumer Protection and Food Safety, 2024)
A simple and effective heuristic approach was developed and validated to predict the concentration of non-relevant metabolites (nrM) of pesticides in groundwater and drinking water resources based on the simulated concentrations in leachate as used in product authorizations. The evaluation of extensive monitoring data for 50 nrM has demonstrated that the heuristic has a high predictive performance, i.e., concentrations of < 10 µg/l in shallow leachate in the unsaturated zone of the soil in 1 m depth are protective of 1 µg/l in groundwater and raw water in 98 % of cases (49/50 nrM). The reason for the excellent predictive power of the heuristic approach is the large concentration attenuation from leachate to groundwater and to raw water, which was determined to be, on average, 25- and 45-fold, respectively.

A structured approach for the compliance analysis of battery systems with regard to the new EU Battery Regulation - Sönke Hansen; Tom Rüther; Mark Mennenga; Christoph Helbig; Gregor Ohnemüller; Filip Vysoudil; Constantin Wolf; Bernd Rosemann; Sandra Pavón; Alexander Michaelis; Thomas Vietor; Frank Döpper; et al. (Resources, Conservation and Recycling, 2024)

Longitudinal relationships between depressive symptoms, functional impairment, and physical activity in later late life - Lisa Y. Xiong; Madeline Wood Alexander; Hugo Cogo-Moreira; Che-Yuan Wu; Michael Eid; Nathan Herrmann; Damien Gallagher; Jodi D. Edwards; Krista L. Lanctôt; Susan Marzolini; David A. Bennett; Jennifer S. Rabin; et al. (GeroScience, 2024)

Real-world characteristics and use patterns of patients treated with vericiguat: A nationwide longitudinal cohort study in Germany - Fabian Kerwagen; Christoph Ohlmeier; Thomas Evers; Stefan Herrmann; Inga Bayh; Alexander Michel; Silvia Kruppert; Joanna Wilfer; Rolf Wachter; Michael Böhm; Stefan Störk (European Journal of Clinical Pharmacology, 2024)
Purpose Vericiguat reduced clinical endpoints in patients experiencing worsening heart failure in clinical trials, but its implementation outside trials is unclear. Methods This retrospective analysis of longitudinally collected data was based on the IQVIA™ LRx database, which includes ~ 80% of the prescriptions of the 73 million people covered by the German statutory health insurance. Results Between September 2021 and December 2022, vericiguat was initiated in 2916 adult patients. Their mean age was 73 ± 13 years and 28% were women. While approximately 70% were uptitrated beyond 2.5 mg, only 36% reached 10 mg. Median time to up-titration from 2.5 mg to 5 mg was 17 (quartiles: 11–33) days, and from 2.5 to 10 mg 37 (25–64) days, respectively. In 87% of the patients, adherence to vericiguat was high as indicated by a medication possession ratio of ≥ 80%, and 67% of the patients persistently used vericiguat during the first year. Women and older patients reached the maximal dose of 10 mg vericiguat less often and received other substance classes of guideline-recommended therapy (GDMT) less frequently. The proportion of patients receiving four pillars of GDMT increased from 29% before vericiguat initiation to 44% afterwards. Conclusion In a real-world setting, despite higher age than in clinical trials, adherence and persistence of vericiguat appeared satisfactory across age categories. Initiation of vericiguat was associated with intensification of concomitant GDMT. Nevertheless, barriers to vericiguat up-titration and implementation of other GDMT, applying in particular to women and elderly patients, need to be investigated further.

Diversified innovations in the health sciences: Proposal for a Diversity Minimal Item Set (DiMIS) - Gertraud Stadler; Marie Chesaniuk; Stephanie Haering; Julia Roseman; Vera Maren Straßburger; Schraudner Martina; Ahmad Aisha-Nusrat; Auma Maisha; Banas Kasia; Borde Theda; Buspavanich Pichit; Dewey Marc; et al. (Sustainable Chemistry and Pharmacy, 2023)

Green batteries for clean skies: Sustainability assessment of lithium‐sulfur all‐solid‐state batteries for electric aircraft - Alexander Barke; Walter Cistjakov; Dominik Steckermeier; Christian Thies; Jan‐Linus Popien; Peter Michalowski; Sofia Pinheiro Melo; Felipe Cerdas; Christoph Herrmann; Ulrike Krewer; Arno Kwade; Thomas S. Spengler (Journal of Industrial Ecology, 2023)
The use of novel battery technologies in short‐haul electric aircraft can support the aviation sector in achieving its goals for a sustainable development. However, the production of the batteries is often associated with adverse environmental and socio‐economic impacts, potentially leading to burden shifting. Therefore, this paper investigates alternative technologies for lithium–sulfur all‐solid‐state batteries (LiS‐ASSBs) in terms of their contribution to the sustainable development goals (SDGs). We propose a new approach that builds on life cycle sustainability assessment and links the relevant impact categories to the related SDGs. The approach is applied to analyze four LiS‐ASSB configurations with different solid electrolytes, designed for maximum specific energy using an electrochemical model. They are compared to a lithium–sulfur battery with a liquid electrolyte as a benchmark. The results of our cradle‐to‐gate analysis reveal that the new LiS‐ASSB technologies generally have a positive contribution to SDG achievement. However, the battery configuration with the best technical characteristics is not the most promising in terms of SDG achievement. Especially variations from the technically optimal cathode thickness can improve the SDG contribution. A sensitivity analysis shows that the results are rather robust against the weighting factors within the SDG quantification method.

The invasive crayfish Faxonius immunis causes the collapse of macroinvertebrate communities in Central European ponds - Alexander Herrmann; Karsten Grabow; Andreas Martens (Aquatic Ecology, 2022)
The invasive crayfish Faxonius immunis is regarded as a threat to amphibians and macroinvertebrates in the Upper Rhine Valley, Germany, eradicating macrophytes and establishing high-density populations in stagnant waters. This study investigates the macroinvertebrate community structure of five conservation ponds south of Karlsruhe, Germany, to identify effects caused by this invasive crayfish. Two of the ponds had a high population density of F. immunis , two were expected to have lower crayfish densities as they had been habitat modified with gravelled water beds as a crayfish management approach, and one pond was known to be free of crayfish but contained fish. The macroinvertebrate communities were analyzed considering their species richness and composition. The relative density of F. immunis within the samples was regarded as a representative indicator for crayfish population density and tested for its influence on the ordination along with habitat composition and abiotic factors using distance-based redundancy analysis. F. immunis was identified as a driving factor of the macroinvertebrate communities of sampled ponds. Additionally, this study indicates that gravelling ground beds as a management method for invasive burrowing crayfish species does not significantly influence the community composition but can minimize indirect effects caused by F. immunis .

Woolly beech aphid infestation reduces soil organic carbon availability and alters phyllosphere and rhizosphere bacterial microbiomes - Karin Potthast; Alexander Tischer; Martina Herrmann; Alexander Weinhold; Kirsten Küsel; Nicole M. van Dam; Beate Michalzik (Plant and Soil, 2022)
Purpose The woolly beech aphid thrives on European beech leaves, which has complex direct and indirect impacts on above- and belowground processes. A mechanistic understanding of insect-mediated changes in organic carbon (OC) availability for microbial life and its implications for element cycling is still lacking. This study aims at disentangling aphid-induced effects on phyllosphere and rhizosphere bacterial communities, as well as investigating feedbacks to OC transfer from the canopy to the mineral soil. Methods Following 2.5 months of infestation, we tracked the fate of OC ( 13 CO 2 pulse-labelling) in several compartments of beech sapling – soil mesocosms over 5 days. In ecosystem solutions, water extracts and soil/plant compartments we determined OC and N and solid δ 13 C. Bacterial community structure (16S rRNA gene targeted amplicon sequencing and quantitative PCR) and metabolite profiles (LC-qTOF-MS) were analysed. Results We found significantly higher aphid-mediated inputs of OC within throughfall. Honeydew-derived C on infested leaves was inconsequential for total phyllosphere bacterial abundances, but verifiably affected the community structure. In all soil compartments, cold-water extractable OC pools declined significantly by frequent inputs of readily available OC. This pattern might relate to reductions in rhizodepositions and altered microbial processing by accelerated soil C-mineralization. As a result, the abundance of metabolites changed significantly in different ecosystem solutions. Conclusions Our findings attest that insect infestations induce distinct direct and indirect effects on plant-insect-microbiome interactions leading to marked alterations in C dynamics. This integrated approach improves our understanding on microbial dynamics and biogeochemistry and evaluates the role of insects for ecosystem processes.

Joint effects of climate, tree size, and year on annual tree growth derived from tree‐ring records of ten globally distributed forests - Kristina J. Anderson‐Teixeira; Valentine Herrmann; Christine R. Rollinson; Bianca Gonzalez; Erika B. Gonzalez‐Akre; Neil Pederson; M. Ross Alexander; Craig D. Allen; Raquel Alfaro‐Sánchez; Tala Awada; Jennifer L. Baltzer; Patrick J. Baker; et al. (Global Change Biology, 2022)
Tree rings provide an invaluable long‐term record for understanding how climate and other drivers shape tree growth and forest productivity. However, conventional tree‐ring analysis methods were not designed to simultaneously test effects of climate, tree size, and other drivers on individual growth. This has limited the potential to test ecologically relevant hypotheses on tree growth sensitivity to environmental drivers and their interactions with tree size. Here, we develop and apply a new method to simultaneously model nonlinear effects of primary climate drivers, reconstructed tree diameter at breast height (DBH), and calendar year in generalized least squares models that account for the temporal autocorrelation inherent to each individual tree's growth. We analyze data from 3811 trees representing 40 species at 10 globally distributed sites, showing that precipitation, temperature, DBH, and calendar year have additively, and often interactively, influenced annual growth over the past 120 years. Growth responses were predominantly positive to precipitation (usually over ≥3‐month seasonal windows) and negative to temperature (usually maximum temperature, over ≤3‐month seasonal windows), with concave‐down responses in 63% of relationships. Climate sensitivity commonly varied with DBH (45% of cases tested), with larger trees usually more sensitive. Trends in ring width at small DBH were linked to the light environment under which trees established, but basal area or biomass increments consistently reached maxima at intermediate DBH. Accounting for climate and DBH, growth rate declined over time for 92% of species in secondary or disturbed stands, whereas growth trends were mixed in older forests. These trends were largely attributable to stand dynamics as cohorts and stands age, which remain challenging to disentangle from global change drivers. By providing a parsimonious approach for characterizing multiple interacting drivers of tree growth, our method reveals a more complete picture of the factors influencing growth than has previously been possible.

Auswirkung des Klimawandels auf die Wasserverfügbarkeit - Anpassung an Trockenheit und Dürre in Deutschland - Jenny Tröltzsch; Ulf Stein; Rodrigo Vidaurre; Benedict Bueb; Hannes Schritt; Martina Flörke; Frank Herrmann; Alexander Wriege-Bechtold (WASSERWIRTSCHAFT, 2021)

Genome‐inferred spatio‐temporal resolution of an uncultivated Roizmanbacterium reveals its ecological preferences in groundwater - Patricia Geesink; Carl‐Eric Wegner; Alexander J. Probst; Martina Herrmann; Hang T. Dam; Anne‐Kristin Kaster; Kirsten Küsel (Environmental Microbiology, 2020)
Summary Subsurface ecosystems like groundwater harbour diverse microbial communities, including small‐sized, putatively symbiotic organisms of the Candidate Phyla Radiation, yet little is known about their ecological preferences and potential microbial partners. Here, we investigated a member of the superphylum Microgenomates ( Cand . Roizmanbacterium ADI133) from oligotrophic groundwater using mini‐metagenomics and monitored its spatio‐temporal distribution using 16S rRNA gene analyses. A Roizmanbacteria‐specific quantitative PCR assay allowed us to track its abundance over the course of 1 year within eight groundwater wells along a 5.4 km hillslope transect, where Roizmanbacteria reached maximum relative abundances of 2.3%. In‐depth genomic analyses suggested that Cand . Roizmanbacterium ADI133 is a lactic acid fermenter, potentially able to utilize a range of complex carbon substrates, including cellulose. We hypothesize that it attaches to host cells using a trimeric autotransporter adhesin and inhibits their cell wall biosynthesis using a toxin–antitoxin system. Network analyses based on correlating Cand . Roizmanbacterium ADI133 abundances with amplicon sequencing‐derived microbial community profiles suggested one potential host organism, classified as a member of the class Thermodesulfovibrionia (Nitrospirae). By providing lactate as an electron donor Cand . Roizmanbacterium ADI133 potentially mediates the transfer of carbon to other microorganisms and thereby is an important connector in the microbial community.

Protective potential of dimethyl fumarate in a mouse model of thalamocortical demyelination - Manuela Cerina; Venu Narayanan; Anna Delank; Patrick Meuth; Stephanie Graebenitz; Kerstin Göbel; Alexander M. Herrmann; Stefanie Albrecht; Thiemo Daldrup; Thomas Seidenbecher; Ali Gorji; Tanja Kuhlmann; et al. (Brain Structure and Function, 2018)

An interstate highway affects gene flow in a top reptilian predator (Crotalus atrox) of the Sonoran Desert - Hans-Werner Herrmann; Krystyn M. Pozarowski; Alexander Ochoa; Gordon W. Schuett (Conservation Genetics, 2017)

The Ocean's Vital Skin: Toward an Integrated Understanding of the Sea Surface Microlayer - Anja Engel; Hermann W. Bange; Michael Cunliffe; Susannah M. Burrows; Gernot Friedrichs; Luisa Galgani; Hartmut Herrmann; Norbert Hertkorn; Martin Johnson; Peter S. Liss; Patricia K. Quinn; Markus Schartau; et al. (Frontiers in Marine Science, 2017)

Large-scale genetic census of an elusive carnivore, the European wildcat (Felis s. silvestris) - Katharina Steyer; Robert H. S. Kraus; Thomas Mölich; Ole Anders; Berardino Cocchiararo; Christiane Frosch; Alexander Geib; Malte Götz; Mathias Herrmann; Karsten Hupe; Annette Kohnen; Matthias Krüger; et al. (Conservation Genetics, 2016)

Approximating the average daily surface albedo with respect to soil roughness and latitude - Jerzy Cierniewski; Arnon Karnieli; Krzysztof Kuśnierek; Alexander Goldberg; Ittai Herrmann (International Journal of Remote Sensing, 2013)

Technology-specific error signatures in the 1000 Genomes Project data - Michael Nothnagel; Alexander Herrmann; Andreas Wolf; Stefan Schreiber; Matthias Platzer; Reiner Siebert; Michael Krawczak; Jochen Hampe (Human Genetics, 2011)

Compositionality of arm movements can be realized by propagating synchrony - Alexander Hanuschkin; J. Michael Herrmann; Abigail Morrison; Markus Diesmann (Journal of Computational Neuroscience, 2011)

Trace elements in buried human bones: intra-population variability of Sr/Ca and Ba/Ca ratios – diet or diagenesis? - Alexander Fabig; Bernd Herrmann (The Science of Nature, 2002)